Sistema de comercialización de la corporación de productores y comercializadores orgánicos Bio taita Chimborazo - Coprobich, comunidad Mishquilli, parroquia Cajabamba, cantón olta, provincia de Chimborazo y su incidencia en el posicionamiento de mercado. periodo 2014 – 2015. - Chucho Guapi, Mayra Verónica (2017)
The present investigation refers to the study of the SYSTEM OF commercialization of THE CORPORATION OF ORGANIC PRODUCERS AND Organic BIO TAITA CHIMBORAZO - COPROBICH, MISHQUILLI COMMUNITY, CAJABAMBA PARK, CANTÓN COLTA, PROVINCE OF CHIMBORAZO AND incident in the POSITIONING OF THE MARKET. PERIOD 2014 - 2015, in order to relate the marketing system and market positioning as a competitive approach to the organization. The research is composed of five chapters in which it is divided: Chapter I: The framework is developed, which consists of problem and problem formulation, objectives and justification. Chapter II: The Theoretical Framework is developed. The same one that consists of the antecedent, theoretical foundation, and the research units that are described as follows: Unit I: Data of the Corporation of Organic Producers and Traders Bio Taita Chimborazo - COPROBICH, Unit II: Marketing system, Unit III : Market positioning, Unit IV: Hypothetical unit, the variables with their respective operationalization. Chapter III: The methodological framework used for research, method, types and designs of research, population and sample, information collection techniques and instruments, information procedure, analysis and interpretation of results and Hypothesis testing. Chapter IV: It contains the conclusions and recommendations established in the investigation. Chapter V: Consists of the proposal or recommendation of the topic. Attached is also the bibliography and annexes to the research.